The System of Sources of Law - Lukács, Krisztina (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
This chapter aims to analyse the system of sources of law in the countries of the CEE region through a comparative constitutional lens. To this end, it first attempts to present and clarify some fundamental concepts that are necessary and relevant to examine the system of sources of law. Subsequently, it outlines the development of the various systems of sources of law from a historical perspective. In light of this general overview, the chapter then turns to each system of sources of law of this region to map and explore them in a comparative way. Accordingly, it describes the major characteristics of legal norms at various levels of the norm hierarchy as well as how they create a system of sources of law. Furthermore, it examines the place and role of international law and EU law. Finally, it outlines how states in the region provide access to legal norms in their respective systems. KEYWORDS: system of sources of law, legal norms, norm hierarchy, constitutions, acts, decrees, regulations, decrees of the local governments, access to legal norms.